Substantiation of financing approach for rural property/Kaimo statinių finansavimo metodo pagrindimas - Lunkevičius, Sigitas; Ustinovičius, Leonas; Zavadskas, Edmundas Kazimieras (Journal of Civil Engineering and Management, 2001)
When resolving issues of rural property revival, it is necessary to deal with the subject of financing. Existing financial methods are aimed at solving specific financial tasks and defining relations of contract parties as well as their distribution of risk/liability in the way specific for those conditions. Different financial schemes have been created for particular cases. In order to activate investments into rural property of Lithuania it is important to devise a financing approach which is useful and economically motivated to all sides of the credit contract. Article in Lithuanian. First Published Online: 30 Jul 2012